PEMANFAATAN LIMBAH CAIR PEMINDANGAN IKAN - Arieyanti Dwi Astuti (Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Pati, 2019)
ENGLISHThe enhancement number of boiled fish production will always followed by the increase of waste volume, especially wastewater that in the process will be dumped into the environment. Whereas, if it used with technology development varieties, boiled fish wastewater potentially produce new products. This is because the content of the materials in boiled fish wastewater that useful, such as proteins, fats, salts, and others. That’s required an effort that is able to utilizing wastewater boiled fish, as well as to create new products from utilization results of the wastewater. This review aims to provide an overview about the use of wastewater boiled fish that has not been widely known and applied to the community, especially in coastal area of Pati Regency which related to the boiled fish industry. Boiled fish wastewater can be utilized as raw material for the manufacture of fish paste, animal feed and organic liquid fertilizer. INDONESIAPeningkatan jumlah produksi pemindangan ikan akan selalu diikuti dengan peningkatan volume limbah, terutama limbah cair yang dalam prosesnya akan dibuang begitu saja ke lingkungan. Padahal jika dimanfaatkan dengan berbagai pengembangan teknologi, limbah cair pemindangan ikan ini berpotensi menghasilkan produk-produk baru. Hal ini dikarenakan adanya kandungan bahan-bahan yang terdapat pada limbah cair pemindangan ikan yang bermanfaat, seperti protein, lemak, garam, dan lain-lain. Untuk itulah diperlukan suatu upaya yang mampu memanfaatkan limbah cair pemindangan ikan, sekaligus menciptakan produk-produk baru dari hasil pemanfaatan limbah cair tersebut. Review ini bertujuan untuk memberikan gambaran mengenai pemanfaatan limbah cair pemindangan ikan yang belum banyak diketahui dan diterapkan pada masyarakat, terutama masyarakat di kawasan pesisir di Kabupaten Pati yang banyak berhubungan dengan industri pemindangan ikan. Limbah cair pemindangan ikan dapat dimanfaatkan menjadi bahan baku pembuatan petis ikan, pakan ternak dan pupuk cair organik.